Investigating the role of exosomal long non-coding RNAs in drug resistance within female reproductive system cancers - Shirani, Nooshafarin; Abdi, Neda; Chehelgerdi, Matin; Yaghoobi, Hajar; Chehelgerdi, Mohammad (Frontiers in Cell and Developmental Biology, 2025)
Exosomes, as key mediators of intercellular communication, have been increasingly recognized for their role in the oncogenic processes, particularly in facilitating drug resistance. This article delves into the emerging evidence linking exosomal lncRNAs to the modulation of drug resistance mechanisms in cancers such as ovarian, cervical, and endometrial cancer. It synthesizes current research findings on how these lncRNAs influence cancer cell survival, tumor microenvironment, and chemotherapy efficacy. Additionally, the review highlights potential therapeutic strategies targeting exosomal lncRNAs, proposing a new frontier in overcoming drug resistance. By mapping the interface of exosomal lncRNAs and drug resistance, this article aims to provide a comprehensive understanding that could pave the way for innovative treatments and improved patient outcomes in female reproductive system cancers.